Early immune adaptation in HIV-1 revealed by population-level approaches - Martin, Eric; Carlson, Jonathan M.; Le, Anh Q; Chopera, Denis R; McGovern, Rachel; Rahman, Manal A; Ng, Carmond; Jessen, Heiko; Kelleher, Anthony D; Markowitz, Martin; Allen, Todd M; Milloy, MJ; et al. (Retrovirology, 2014)
The reproducible nature of HIV-1 escape from HLA-restricted CD8+ T-cell responses allows the identification of HLA-associated viral polymorphisms “at the population level” – that is, via analysis of cross-sectional, linked HLA/HIV-1 genotypes by statistical association. However, elucidating their timing of selection traditionally requires detailed longitudinal studies, which are challenging to undertake on a large scale. We investigate whether the extent and relative timecourse of immune-driven HIV adaptation can be inferred via comparative cross-sectional analysis of independent early and chronic infection cohorts.